THE COMMUNITY EMPOWERMENT STRATEGY IN FACING THE POTENTIAL EARTHQUAKES IN SURABAYA: A LITERATURE REVIEW - Kurniawan, Dedy; Handayani, Vitria Wuri; Pamudi, Berwi Fazri (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2021)
In all communities, there is local wisdom and values that are formed from the disaster experience and the efforts to manage the disaster in the past. There is a lot of local wisdom that develops in the community, so each region will mark the earthquake events in its way. Every disaster event by the community is marked by various unique ways so that future generations could remember and learn from the previous disasters. This diversity of local wisdom needs to be deepened through literature studies so that lessons can be obtained from other regions to inspire the implementation of community empowerment in the city of Surabaya to face the potential for earthquakes. To analyze how community empowerment can enhance the Surabaya community earthquake disaster resilience. This is a Literature Review, that collected articles using the Google Scholar and PubMed search engines. The author filtered and selected according to inclusions criteria. The results of the literature study obtained a proposed strategy design that can be used to increase participation in the context of Surabaya community empowerment. This literature could be accommodating socio-spiritual values, increasing disaster knowledge for all levels of society, and strengthening community social systems to the lowest level.